Aggregate supply and demand in Ukraine during its way from command to market relations - Tkachuk (Stakhurska), Svitlana; Avramenko, Olga (My University, 2006)
The situation that took place in economy of Ukraine with the point of balance between aggregate supply and demand in the period of transformation from command economy to market relations is examined.
Keywords: aggregate supply; aggregate demand; point of macroeconomic balance; сукупна пропозиція; сукупний попит; точка макроекономічної рівноваги; кафедра маркетингу